DIGITAL MAP APLICATION IN ANALYSIS OF PUBLIC TRANSPORT ROUTES WITH BUS IN BANDUNG CITY AS THE CASE OF STUDY - AL FARISI (NIM : 15007136); Pembimbing : Ir. R. Sony Sulaksono Wibowo, MT. Ph.D, NAVISYAH
Bandung is the capital city of West Java province with a population of 2,4 million people. To support the daily movement of its people, Bandung has 11 city bus routes operated by Perum DAMRI. This study aims to develop a digital map application as an evaluation tool of city bus routes by considering demand point and other types of public transport routes. Application of digital map used is MapInfo version 7,5. Demand of public transit service is defined as the number of activity points without distinction of public transit needs. The data used are secondary data obtained from the relevant agencies. The map contains 14 themes that consist of information about the district, village, road network, urban transport routes, TMB Bus routes, DAMRI Bus routes, terminals, industrial sites, high schools, colleges, hospitals, markets and malls, government office, and banks. Secondary data owned by relevant agencies are used as reference in drawing the map. Evaluation is done on the DAMRI Bus route related with the mileage, coverage area, movement destinations and population within the coverage area, and also overlapping with city transportation. Coverage area is the area within a radius of 400 meters from DAMRI Bus route. The value is assumed as walking distance allowable for city bus routes. The destinations of movement in the coverage area are calculated manually. Overlapping analysis between routes of DAMRI Bus and urban transportation is performed for each route segment. Within the scope of Bandung city, DAMRI Bus Line VI is a trajectory that has the longest route mileage and the largest coverage area. DAMRI Bus Line I is the trajectory with the largest number of movement destinations in the coverage area and DAMRI Bus Line IX is a trajectory with the largest estimated population in the coverage area. Long distance routes potentially produce a large coverage area. Diversion route of DAMRI Bus Line IX and DAMRI Bus Line XI by passing Surapati Street and Rumah Sakit Street produce a larger potential of demand center than existing routes but it is followed by more operating costs and distance of overlap with urban transportation.